Effectiveness of stress management interventions for nursing students: a systematic review and meta‐analysis - Xuan, Ji; Xiaoyan, Guo; Kim, Lam Soh; Japar, Salimah; LiPing, He (John Wiley & Sons, 2024)
Elevated stress levels are related to diminished mental health, potentially leading to decreased well-being and performance of nursing students. While researchers have focused on developing stress management interventions, there is a need to synthesize the evidence. A systematic review with meta-analysis was conducted to assess the evidence for the effectiveness of stress management interventions in nursing students. A systematic literature search identified controlled stress management interventions employing a validated psychological or physiological stress measure. Forty-one studies were included, with 36 forming a pool of 2715 participants in the meta-analysis. The overall effect on psychological stress was positive. Intervention type, delivery modality, intervention duration in weeks, and number of sessions were moderators of intervention effectiveness, with more significant effects for mind–body programs, on-site delivery methods, durations of 9–12 weeks, and 15–30 sessions. For physiological stress, the biomarkers of blood pressure, heart rate, and cortisol levels decreased significantly. Future research is necessary for promising outcomes related to currently underrepresented indicators and to investigate the long-term effects of interventions.